EFFECT OF VITAMIN E SUPPLEMENTATION TOWARDS DEVELOPMENT OF THE ANAEROBIC POWER AND PHOSPHATE MEDIATED RECOVERY OF SPRINTERS - Hoque, Aminul; Bandopadhyay, Pathikrit (International Journal of Applied Pharmaceutics, 2016)
Objective: Anaerobic exercise has been considered as short duration high-intensity exercise requires anaerobic conversion of available biological phosphates to its active phosphorylated form by the enzymatic action of creatine kinase. Several research studies have been pointed out the role of vitamin supplementation and amelioration from exercise-induced oxidative stress. Vitamin E is a potential lipid soluble antioxidant has profound roles in amelioration of free radicals generated during endurance exercise. In this study, our attempt is to observe the effect of vitamin E towards development of anaerobic power and recovery by restoration of biological phosphates. Methods: In this study, we have taken 30 male subjects from 100m and 200m sprinters of which half of them were given vitamin E supplement. The serum creatine and creatine kinase activity were measured in 100m and 200m sprinters after their exercise. Rapid Anaerobic based Sprint test and phosphate recovery test were applied to test the sprinting ability and recovery. Results: It was observed that in both 100 and 200m sprinters subjects with vitamin E supplementation have better sprinting ability as confirmed from RAST test and quicker recovery than subjects whom vitamin E supplementation was not given; which are correlated with serum creatine kinase and creatine level suggesting that the vitamin E can improve in anaerobic performance. Conclusion: From this study, it can be concluded that vitamin E supplementation develops the anaerobic power and phosphate mediated recovery of hundred meters (100m) and two hundred meters (200m) sprinters. Keywords: Vitamin E, Anaerobic exercise, Creatine kinase, Rapid Anaerobic based Sprint Test, Phosphate recovery